Open pelvic fractures – results of a multi-institutional study - Mladenović Marko; Stoiljković Predrag; Lalić Ivica; Harhaji Vladimir; Krstić Andrija (Vojnosanitetski Pregled)
Open pelvic fractures are devastating injuries, rare, and with high mortality. Leading causes of mortality are: haemorrhage, infection and associated injuries. The aim of this paper is to point out methods of treating these injuries and great number of prognostic mortality factors. Material - in period from January 2011 to December 2015, 221 patients with pelvis ringfracture were treated in three large clinical centers of Serbia, of which 13(5%) had an open fracture type. We have classified pelvic ring fractures according to the Young - Burgess classification. We have classified injuries according to Gustilo at I, II, and III degree, and the location of the wound according to Faringer classification was distributed in zone I, II and III. Urogenital and intra-abdominal injuries were monitored, and severity of injuries was determined according to Severity Score Injury (ISS) and Trauma Score (TS). Results - there were 6(46%) women and 7(54%) men at the average age of 41(13 - 76). Injuries from traffic trauma are dominant. The most common cause of pelvic ring fracture is an anterior posterior compression - 6(46%), lateral compression - 4(31%) and vertical force in 3 (23%) patients. Dominant injuries are type I and II according to Gustilo, and zone I according to Faringer classification. There were 6 (46%) patients with urogenital injuries, and the same number with intra-abdominal injuries, of which 3(23%) patients have been treated with colon resection and diversion. Due to abundant hemorrhage and hypovolemic shock 2 patients died, and another one died after three days due to sepsis and multisystem organ failure (MSOF). Conclusion - Open pelvic fractures have high mortality rate, due to: haemorrhage, infection, associated abdominal and genitourinary tract injuries, ISS> 25, TS <8 and age of patient >65 years.